The Impact of Problem Based Learning Model Base on Practicum Activities on The Critical Thinking Ability of High School Student on Respiration System Material - Kesha, Tiara; Rasyidah, Rasyidah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Observations carried out at Senior High School of SMA Ar Rahman found that students' critical thinking abilities were still low, especially in the respiratory system material. The aim of this research is to determine the effect of the problem based learning model on students' critical thinking abilities through practicum on respiratory system material. The samples used were second grade class (XI-MIPA 1) as the experimental-class and XI-MIPA 2 as the control-class. The quasi-experimental research uses a posttest only control design. The variable measured is students' critical thinking abilities obtained from the pretest-posttest scores tested by the t-test. Student practicum activities, student responses, and teacher responses were analyzed using percentage qualitative descriptive analysis. The results showed the average critical thinking ability score for the experimental class was 76.93 while the control was 65.67. The results of the t-test show that there is a significant influence between biology learning using the Problem Based Learning model on students' critical thinking abilities at SMA Ar Rahman High School. The implication is that implementing the PBL model in respiratory system material can serve as an effective pedagogical alternative for educators on SMA Ar Rahman high school to foster higher-order thinking skills in students, which are essential in addressing 21st-century learning challenges. This study provides empirical evidence for the development of a biology learning model based on Problem-Based Learning (PBL) integrated with practicum activities